Grassroots and Youth-Led Climate Solutions From The Gambia - Bonell, Ana; Badjie, Jainaba; Jammeh, Sariba; Ali, Zakari; Hydara, Muhammed; Davies, Adesina; Faal, Momodou; Ahmed, Aliyu Nuhu; Hand, William; Prentice, Andrew M.; Murray, Kris A.; Scheelbeek, Pauline (Frontiers in Public Health, 2022)
Climate change and environmental degradation are among the greatest threats to human health. Youth campaigners have very effectively focused global attention on the crisis, however children from the Global South are often under-represented (sometimes deliberately) in the dialogue. In The Gambia, West Africa, the impacts of climate change are already being directly experienced by the population, and this will worsen in coming years. There is strong government and community commitment to adapt to these challenges, as evidenced by The Gambia currently being the only country on target to meet the Paris agreement according to the Nationally Determined Contributions, but again children's voices are often missing—while their views could yield valuable additional insights. Here, we describe a “Climate Change Solutions Festival” that targeted and engaged school children from 13 to 18 years, and is to our knowledge, the first peer-to-peer (and student-to-professional) learning festival on climate change solutions for students in The Gambia. The event gave a unique insight into perceived climate change problems and scalable, affordable and sometimes very creative solutions that could be implemented in the local area. Logistical and practical methods for running the festival are shared, as well as details on all solutions demonstrated in enough detail to be duplicated. We also performed a narrative review of the most popular stalls to explore the scientific basis of these solutions and discuss these in a global context. Overall, we find extremely strong, grass-roots and student engagement in the Gambia and clear evidence of learning about climate change and the impacts of environmental degradation more broadly. Nevertheless, we reflect that in order to enact these proposed local solutions further steps to evaluate acceptability of adoption, feasibility within the communities, cost-benefit analyses and ability to scale solutions are needed. This could be the focus of future experiential learning activities with students and partnering stakeholders.